Pricing institutions and the welfare cost of adverse selection - Weyl,EG; Veiga,A (American Economic Journal: Microeconomics, 2017)
To mitigate adverse selection in insurance markets, individuals are often mandated to buy at least a baseline plan, but may choose to opt into a premium plan. In some markets, such as US health exchanges, each plan is responsible for the full expenses of those who buy it ("total pricing"). In other markets, such as the privately supplied "Medigap" top-ups to traditional government-provided Medicare, premium providers are only responsible for the incremental expenses they top up ("incremental pricing"). For parameter values calibrated to health exchanges, the shift from total to incremental pricing reduces the welfare loss from adverse selection by an order of magnitude.